1995
DOI: 10.1017/s0043174500081248
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rye Cover Crops on Weed Populations in a Tomato Cropping System

Abstract: A reduced-till (RT) experiment determined the effect of rye seeding density and method of kill on rye biomass persistence, weed suppression, and tomato yield. ‘Wheeler’ rye was seeded at 56, 110, and 170 kg ha−1in the fall of 1988 and 1989 in Champaign, IL; Lexington, KY; and Lafayette, IN. One wk before transplanting tomatoes, rye was desiccated either by applying glyphosate at 1.1 kg ha−1and mowing (RT-glyphosate) or by mowing alone (RT-mowed). Both methods left rye residues on the soil surface as a mulch. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
55
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 23 publications
7
55
0
1
Order By: Relevance
“…However, the evaluated studies suggested that there could be confounding impact between the cover crop and its method of termination on weed suppression (Hoffman et al, 1993;Masiunas et al, 1995;Carrera et al, 2004). However, the evaluated studies suggested that there could be confounding impact between the cover crop and its method of termination on weed suppression (Hoffman et al, 1993;Masiunas et al, 1995;Carrera et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the evaluated studies suggested that there could be confounding impact between the cover crop and its method of termination on weed suppression (Hoffman et al, 1993;Masiunas et al, 1995;Carrera et al, 2004). However, the evaluated studies suggested that there could be confounding impact between the cover crop and its method of termination on weed suppression (Hoffman et al, 1993;Masiunas et al, 1995;Carrera et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluated studies suggested that there could be confounding impact between the cover crop and its method of termination on weed suppression (Hoffman et al, 1993;Masiunas et al, 1995;Carrera et al, 2004). For example, cereal rye and hairy vetch terminated by mowing resulted in regrowth of the cover crop a few days after termination, causing competition with the main crop and consequent yield reductions (Masiunas et al, 1995;Carrera et al, 2004). It is important to note that similar weed suppression reported with the termination method may not result in similar main crop yields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cover crop use in cooler climates may slow soil warming and delay crop production (Abdul-Baki et al 1996;Hutchinson and McGiffen 2000;Knavel and Herron 1986;Masiunas et al 1995). Cover crops may also increase water use in areas with limited rainfall.…”
mentioning
confidence: 99%
“…Some cover crops, including cereal rye, have well-documented allelopathic properties (Kruidhof et al 2009;Putnam and Duke, 1978). In one study, cereal rye was the most suppressive cover crop used in a variety of cropping systems for early season broadleaf weeds (Nagabhushana et al 2001) and also provided significant suppression of weeds in transplanted tomato (Solanum lycopersicum L.) (Masiunas et al 1995). Both cereal rye and barley (Hordeum vulgare L.) have been shown to provide significant weed-suppressive traits in no-till corn (Zea mays L.) and soybean [Glycine max (L.) Merr.]…”
mentioning
confidence: 99%